2013
DOI: 10.1111/jir.12047
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from sudden unexpected death in epilepsy (SUDEP) in a cohort of adults with intellectual disability

Abstract: The authors believe that a comprehensive risk management under a multiagency/multidisciplinary framework should be undertaken for all adults with ID and epilepsy in day-to-day clinical practice to reduce mortality in people with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 48 publications
1
36
0
1
Order By: Relevance
“…Other studies have reported increased mortality rates among people with intellectual disability and epilepsy, 10 with a particular concern over the contribution of sudden unexpected death associated with epilepsy. 20,21 Mortality among people with Down syndrome has been more widely studied. [22][23][24][25] The findings from these investigations are consistent with the high risk of death we found among people with Down syndrome.…”
Section: Contextmentioning
confidence: 99%
“…Other studies have reported increased mortality rates among people with intellectual disability and epilepsy, 10 with a particular concern over the contribution of sudden unexpected death associated with epilepsy. 20,21 Mortality among people with Down syndrome has been more widely studied. [22][23][24][25] The findings from these investigations are consistent with the high risk of death we found among people with Down syndrome.…”
Section: Contextmentioning
confidence: 99%
“…This compares with the HRs we found of 6.0 and 3.2 before adjusting for mortality (see Table 23). In the Leicestershire study, 133 elevated SMRs for adults with ID with epilepsy were seen in both men (SMR 3.2) and women (SMR 5.6), with both rising dramatically when the outcome was restricted to SUDEP, identified from case notes and post-mortem reports. In Ontario, elevated mortality with epilepsy for people with ID compared with that for those without epilepsy was about 1.8 times higher for ages 20-60 years, 125 compared with our estimate of 1.6-1.7 (see Table 24).…”
Section: Mortalitymentioning
confidence: 99%
“…133,134 A Swedish study 135 of 1478 people with ID found associations between epilepsy and mortality between 1987 and 1992, with an estimated SMR of 5.0 for those with epilepsy compared with 1.6 for those without epilepsy. This compares with the HRs we found of 6.0 and 3.2 before adjusting for mortality (see Table 23).…”
Section: Mortalitymentioning
confidence: 99%
“…16,23,[25][26][27][28][29][30][31][32]56 The remit of comment and investigation of SMR of risk factors of these 10 studies was ambiguous and diverse. Some articles commented on epilepsy SMR in people without ID and some reported on epilepsy SMR in the background of ID or CP or neurological damages.…”
Section: Resultsmentioning
confidence: 95%
“…The two major epilepsy related causes of death in ID are, sudden unexpected death in epilepsy (SUDEP) and status epilepticus are significantly over represented in this population. 16 With regard to SUDEP and ID, Tellez-Zenteno et al in their systematic review found the risk to be 3.4 times higher than the general population with epilepsy. 17 Walczak et al in their cohort study identified a 5 times higher risk of SUDEP, with ID being an independent risk factor.…”
Section: Introductionmentioning
confidence: 97%